Eleanor H. Porter's Pollyanna : A Children's Classic at 100 - Kokkola, Lydia, 1967-; Harde, Roxanne (Book collections on Project MUSE., 2014)
Appearing first as a weekly serial in The Christian Herald, Eleanor H. Porter's Pollyanna was first published in book form in 1913. This popular story of an impoverished orphan girl who travels from America's western frontier to live with her wealthy maternal Aunt Polly in the fictional east coast town of Beldingsville went through forty-seven printings in seven years and remains in print today in its original version, as well as in various translations and adaptations. The story's enduring appeal lies in Pollyanna's sunny personality and in her glad game, her playful attempt to.